Syntax for language teachers: Revisiting the nature of language - Muhammad Tolkhah Adityas; Ikmi Nur Oktavianti; Icuk Prayogi (Universitas Ahmad Dahlan)
Teaching language is not only a matter of delivering language materials to the learners (e.g., using various methods or media), but it is also about what is thought and what is understood by the teachers that might contribute indirectly in designing and delivering the materials. Those aspects are the manifestations of teachers’ knowledge about language. Teachers who have sufficient understanding on language will be able to conduct better practice of language teaching since they understand what they are teaching. It is then intriguing to discuss the roles of syntax for language teachers: what can teachers benefit from it? This paper aims at revisiting the importance of syntax for language teachers by looking at the nature of language and the nature of syntax. This paper reviews the available relevant literature. The result of discussion emphasizes the potentiality of syntax to equip teachers with adequate knowledge on language, language structure and how to cope with changes in language. Moreover, reading syntax research can enrich teachers’ knowledge. This knowledge can be of beneficial for teachers, for instance in designing the language content of teaching materials. These are not surprising since language teachers are teaching language; therefore, they should also consider language characteristics of the language they are teaching.